Expression Profiles of CircRNA and mRNA in Lacrimal Glands of AQP5–/– Mice With Primary Dry Eye - Liu, Yaning; Di, Guohu; Hu, Shaohua; Zhao, Tianyu; Xu, Xinkai; Wang, Xiaoyi; Chen, Peng (Frontiers in Physiology, 2020)
Purpose: This work aimed to identify differentially expressed circular RNAs (circRNAs) and elucidate their potential function in aquaporin 5 (AQP5) knockout (AQP5–/–) mice with the primary dry eye phenotype. Methods: A slit lamp examination was performed on AQP5–/– mice to assess corneal epithelial defects using fluorescein sodium staining. Hematoxylin–eosin staining and transmission electron microscopy analysis were performed to identify structural changes in lacrimal gland epithelial cells due to AQP5 deficiency. The expression profiles of circRNA and messenger RNA (mRNA) were determined by a microarray analysis. The selected circRNA was verified by quantitative real-time reverse transcription-polymerase chain reaction (qRT-PCR). Gene Ontology and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analyses were performed to predict the biological functions and the potential pathways of parental genes involved in lacrimal gland epithelial cell changes. According to the bioinformatics analysis of identified circRNAs, we predicted a circRNA–miRNA–mRNA network of phagosomes. Results: The AQP5–/– mice spontaneously exhibit dry eye symptoms, wherein the AQP5 deficiency changes the structure of lacrimal gland epithelial cells. The analysis revealed that, compared to AQP5+/+ mice, 30 circRNAs in the lacrimal glands of AQP5–/– mice were differentially expressed (fold change ≥ 2.0, p < 0.05). Nine upregulated circRNAs were identified using qRT-PCR, and nine upregulated validated circRNAs, 40 altered microRNAs (miRNAs), and nine upregulated mRNAs were identified through a network analysis. The KEGG analysis showed that these nine target genes were expressed in phagosomes. Conclusion: The AQP5–/– mice have primary and stable dry eye phenotypes from birth. We identified differently expressed circRNAs in the lacrimal glands of AQP5–/– and AQP5+/+ mice, predicting a circRNA–miRNA–mRNA network of phagosomes. CircRNA likely plays an important role in lacrimal gland epithelial cell pathogenesis. Therefore, it is reasonable to use circRNA as a potential therapeutic agent for the treatment of dry eyes.